Analisis Strategi Pemasaran Gurita Di Kecamatan Sekotong Kabupaten Lombok Barat - Fadli, Fadli; Atsiqah, Fadhlin Akbar; Rozi, Tapaul; Hidayati, Lilik (LPPM Universitas Mataram, 2025)
Octopus is one of the fisheries products that has high economic value and stable demand, especially from the export market. This study aims to analyze the marketing strategy of octopus in Sekotong District, West Lombok Regency, using a descriptive approach through SWOT analysis and EFAS and IFAS matrices. Data were collected through observation, interviews, and distributing questionnaires to 30 respondents consisting of fishermen and collectors. The results of the study indicate that the marketing strategy of octopus still faces a number of challenges, such as the weak bargaining position of fishermen, limited post-harvest handling facilities, minimal access to promotion, and high dependence on middlemen. The SO (Strength-Opportunity) strategy is the most recommended strategy, especially by encouraging digital promotion and the formation of fishermen's institutions to expand market access.